Differentiation for Private Banking inMalaysia: A study of Service Preferences of Malaysia HWI Segment - Lee, Sook Fong (2010)
This paper aims to investigate service preferences among customers/clients in the Malaysian HNWI segment – with the aim being to develop a differentiation strategy for private banking in Malaysia. The study will further indentify the differences in perceptions about determinates of private banking in Malaysia by several demographic groups such as age, gender, wealth source, risk profile etc. A survey was carried out to test the three major areas that influence the client value and services preference which highlighted in the pertinent literature review. The data are further tested using reliability analysis, descriptive analysis and factor analysis to indentify the factors and their impact on client value and service preference. It is hoped that the findings will provide guidance to management to focus on specific initiative and efforts to improve the conditions that will drive the business of Malaysia Private Banking